Person-centered studies in psychology of science
1 online resource
Keywords: "This unique collection examines 'the acting person' as an important unit of analysis for science studies, using an integrative approach of in-depth case studies to explore the cognitive, social, cultural, and personal dimensions of a series of key figures in the sciences, from Goethe to Kepler to Rachel Carson. Opening up key questions about what science is, and what comprises a scientist, the volume offers an accessible introductory approach to psychology of science, a growing area in Science and Technology Studies (STS). Case studies focus on the psychological contexts of the contributions for which the scientist is known. Without diminishing its epistemic authority, science is presented as a psychologically saturated human activity, one that is especially illustrative of the way social, cognitive, and personal processes intermingle to both facilitate and impede scientific accomplishment. Each case study ends with a set of discussion questions, providing a valuable resource for student reflection and discussion, inviting analysis of similarities and differences in science in the context of very different lives and different projects. Person-Centered Studies in Psychology of Science is essential reading for scholars and graduates interested in the psychology of science, personality theory, social, or cognitive psychology, general psychologists and theoretical psychologists"--